Astaxanthin Inhibits Interleukin-6 Expression in Cerulein/Resistin-Stimulated Pancreatic Acinar Cells - Min Seung Kwak; Joo Weon Lim; Hyeyoung Kim (Mediators of Inflammation)
Acute pancreatitis is a common clinical condition with increasing the proinflammatory mediators, including interleukin-6 (IL-6). Obesity is a negative prognostic factor in acute pancreatitis. Obese patients with acute pancreatitis have a higher systemic inflammatory response rate. Levels of serum resistin, an adipocytokine secreted by fat tissues, increase with obesity. Cerulein, a cholecystokinin analog, induces calcium (Ca2+) overload, oxidative stress, and IL-6 expression in pancreatic acinar cells, which are hallmarks of acute pancreatitis. A recent study showed that resistin aggravates the expression of inflammatory cytokines in cerulein-stimulated pancreatic acinar cells. We aimed to investigate whether resistin amplifies cerulein-induced IL-6 expression and whether astaxanthin (ASX), an antioxidant carotenoid with anti-inflammatory properties, inhibits ceruelin/resistin-induced IL-6 expression in pancreatic acinar AR42J cells. We found that resistin enhanced intracellular Ca2+ levels, NADPH oxidase activity, intracellular reactive oxygen species (ROS) production, NF-κB activity, and IL-6 expression in cerulein-stimulated AR42J cells, which were inhibited by ASX in a dose-dependent manner. The calcium chelator BAPTA-AM inhibited cerulein/resistin-induced NADPH oxidase activation and ROS production. Antioxidant N-acetyl cysteine (NAC) and ML171, a specific NADPH oxidase 1 inhibitor, suppressed cerulein/resistin-induced ROS production, NF-κB activation, and IL-6 expression. In conclusion, ASX inhibits IL-6 expression, by reducing Ca2+ overload, NADPH oxidase-mediated ROS production, and NF-κB activity in cerulein/resistin-stimulated pancreatic acinar cells. Consumption of ASX-rich foods could be beneficial for preventing or delaying the incidence of obesity-associated acute pancreatitis.